I Cannot Write My Life Islam, Arabic, and Slavery in Omar Ibn Said's America. - Lo, Mbaye (Islamic Civilization and Muslim Networks Series., 2023)
"This work centers on the life and writing of Omar Ibn Said, born in 1770 in a border region between Senegal and Mauritania that played a significant role in Islamic nations. Omar studied for 25 years at an Islamic seminary and was poised to become a leader in the faith, but after being captured by an invading army, he fell into the hands of transatlantic slave traders. He was sold to a plantation owner near Charleston, South Carolina, in 1808. What we know of Omar's life comes largely from a series of brief autobiographical writings and transcriptions, comprising the only known narrative written in Arabic by an enslaved person in North America. In this book, Mbaye Lo and Carl Ernst weave fresh and accurate translations of Omar's writing together with context and interpretation to provide the fullest possible account of this West African Islamic scholar's life and significance"--